2017
DOI: 10.1098/rstb.2016.0458
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution between transposable elements and recombination

Abstract: One of the most striking patterns of genome structure is the tight, typically negative, association between transposable elements (TEs) and meiotic recombination rates. While this is a highly recurring feature of eukaryotic genomes, the mechanisms driving correlations between TEs and recombination remain poorly understood, and distinguishing cause versus effect is challenging. Here, we review the evidence for a relation between TEs and recombination, and discuss the underlying evolutionary forces. Evidence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
284
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(300 citation statements)
references
References 119 publications
13
284
2
1
Order By: Relevance
“…Recombination rates vary across chromosomes in many organisms and their distribution often correlates with other genomic features. For instance, in most vascular plant species, recombination rates are significantly positively correlated with the density of genes and GC content, and negatively correlated with the abundance of repetitive elements (Paape et al , ; Glémin et al , ; Tiley and Burleigh, ; Kent et al , ). We showed that the patterns of correlation between recombination rate and genomic features mainly followed this general pattern in the M. polymorpha genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination rates vary across chromosomes in many organisms and their distribution often correlates with other genomic features. For instance, in most vascular plant species, recombination rates are significantly positively correlated with the density of genes and GC content, and negatively correlated with the abundance of repetitive elements (Paape et al , ; Glémin et al , ; Tiley and Burleigh, ; Kent et al , ). We showed that the patterns of correlation between recombination rate and genomic features mainly followed this general pattern in the M. polymorpha genome.…”
Section: Discussionmentioning
confidence: 99%
“…The high relatedness and spatial proximity of the four populations investigated here, considered to be predominantly selfing (Rogivue et al, ), supports the assumption that both substitution and transposition rates are negligible, arguing for drift or selection as the main drivers of observed patterns for SNPs versus TEs. However, it remains elusive to what extent polymorphic TEs modify the local recombination rate (He & Dooner, ; Kent, Uzunović, & Wright, ; Zamudio et al, ) and may thus influence the fixation of SNPs and polymorphic TEs. The unprecedented resolution of SNP and TE diversity across natural landscapes presented may serve future studies assessing the evolutionary forces driving genome‐wide variation within and among populations, at best complemented by functional studies on the fitness relevance of the genomic variation observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains elusive to what extent polymorphic TEs modify the local recombination rate (He & Dooner, 2009;Kent, Uzunović, & Wright, 2017;Zamudio et al, 2015) and may thus influence the fixation of SNPs and polymorphic TEs. The unprecedented resolution of SNP and TE diversity across natural landscapes presented may serve future studies assessing the evolutionary forces driving genome-wide variation within and among populations, at best complemented by functional studies on the fitness relevance of the genomic variation observed.…”
Section: Possible Adaptive Impact Of the Variantsmentioning
confidence: 99%
“…The relationship between gene density, TE density, and recombination rate has been a long-453 standing discussion (reviewed in Kent et al 2017). It is difficult to parse out these relationships 454 because there are many factors influencing distribution of TEs, genes, and crossovers.…”
Section: Recombination and Genomic Features 452mentioning
confidence: 99%
“…It has been suggested that active silencing of TEs could lead to the silencing or suppression of 464 recombination around those regions (Kent, Uzunović, and Wright 2017). Therefore, it is difficult 465 to determine whether or how TE density and gene density affect recombination rates.…”
Section: Recombination and Genomic Features 452mentioning
confidence: 99%